A quick-setting agent for reducing the rebound of shotcrete and its preparation method

By using a quick-setting agent containing aluminum fluorosilicate, aluminum sulfate, corrosion inhibitor and other components in sprayed concrete, the problem of excessive rebound rate in sprayed concrete is solved, and the rebound rate is reduced and durable is improved. and the effect of extending service life.

CN118993611BActive Publication Date: 2025-02-25LIAONING PENGSHUO TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411096942.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-12
Publication Date
2025-02-25
Estimated Expiration
2044-08-12

AI Technical Summary

Technical Problem

The rebound rate in existing spray concrete construction is too large, resulting in waste of materials, affecting construction efficiency and safety, and putting pressure on the environment.

Method used

A quick-coagulant including aluminum fluorosilicate, aluminum sulfate, corrosion inhibitor, aluminum magnesium silicate and organically modified aluminum hydroxide are used to mix evenly and form a suspension system, diethanolamine, triethanolamine and propylene are added. Triol, a quick-coagulant used to reduce the rebound of sprayed concrete.

Benefits of technology

This quick-setting agent can significantly reduce the rebound rate of sprayed concrete, improve the durability, corrosion resistance and crack resistance of concrete, extend the service life of structural buildings, and improve the comprehensive performance of concrete.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses an accelerator for reducing the rebound of shotcrete and a preparation method thereof. The accelerator comprises the following raw material components in parts by weight: 30-40 parts of aluminum fluorosilicate material, 20-30 parts of aluminum sulfate, 10-20 parts of modified polyethylene, which are stirred evenly until completely dissolved, 10-20 parts of magnesium aluminum silicate, 10-15 parts of organic modified aluminum hydroxide, which are stirred continuously until a uniform suspension system is formed, and 5-10 parts of diethanolamine, 3-5 parts of triethanolamine, and 2-3 parts of propylene glycol are added. The accelerator masterbatch used in shotcrete can make the concrete quickly coagulate and harden and can reduce the rebound rate of the concrete, so that the comprehensive performance of the concrete is better, and the durability, corrosion inhibition and crack resistance of the concrete can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of building materials, and particularly relates to an accelerating setting agent for reducing the rebound of shotcrete and a preparation method thereof. Background Art

[0002] Under the situation of large-scale construction and development of national transportation, mining, structural reinforcement and underground projects, projects such as highway tunnels, urban underground rail transit and underground engineering support projects have increased rapidly. Shotcrete has been widely used in construction operations in special environments such as mines, underground, tunnels and structural reinforcement due to its advantages of short setting time, high early strength, simple process and flexible operation methods. Shotcrete is mainly used as temporary support in domestic highway tunnels. During the construction of shotcrete operations, the three processes of concrete transportation, pouring and compaction can be combined into one process, which simplifies the construction process, is suitable for operations in narrow areas, and thin layers of concrete can be applied in different directions.

[0003] As one of the main forms of support for tunnels and underground projects, with the further development of infrastructure construction, the use of shotcrete has increased dramatically with the increase in engineering projects. At the same time, in my country's existing shotcrete construction, due to unreasonable proportions, unclear sprayer control parameters, and excessive rebound rate during the spraying process, a large amount of material waste is caused, which affects the quality of shotcrete and poses certain safety hazards to the sprayers. At the same time, it also causes unnecessary material recycling and transportation, which not only affects construction efficiency, but also wastes materials and puts great pressure on the environment. Therefore, this paper introduces a quick-setting agent that reduces the rebound rate of shotcrete and can improve the durability, corrosion inhibition and crack resistance of concrete. Summary of the invention

[0004] In view of this, the present invention provides an accelerating setting agent for reducing the rebound rate of shotcrete and a preparation method thereof in order to solve the shortcomings and defects of the single-function accelerating setting agent for reducing the rebound of shotcrete in the prior art.

[0005] Specifically, the following technical solutions are included:

[0006] A quick-setting agent for reducing the rebound rate of shotcrete comprises the following raw material components in parts by weight: 30-40 parts of aluminum fluorosilicate material, 20-30 parts of aluminum sulfate, 10-20 parts of corrosion inhibitor, which are stirred evenly until completely dissolved, 10-20 parts of magnesium aluminum silicate, 10-15 parts of organic modified aluminum hydroxide, which are stirred continuously until a uniform suspension system is formed, and 5-10 parts of diethanolamine, 3-5 parts of triethanolamine, and 2-3 parts of propylene glycol are added.

[0007] The preparation method of the corrosion inhibitor is as follows: 1,4,7-triazacyclononane and acetonitrile are uniformly mixed in a mass ratio of 1:12-13, and a tert-butyl bromoacetate solution corresponding to tert-butyl bromoacetate with a mass of 2 times that of 1,4,7-triazacyclononane is uniformly added at 0-4°C and 200-300r / min within 2-4 hours, the temperature is raised to room temperature, stirring is continued for 22-26 hours, filtering, and drying at 80-85°C for 5-7 hours to obtain a pre-modified corrosion inhibitor; the pre-modified corrosion inhibitor, N,N-diisopropylethylamine, 4-bromo-2-nitroaniline and acetonitrile are mixed in a mass ratio of 1:1.5-2.5: The mixture was stirred at 200-300 r / min for 22-26 h, dried at 80-85°C for 5-7 h, ethyl acetate was added in an amount 3-5 times the mass of N,N-diisopropylethylamine, washed with deionized water for 3-5 times, and dried at 70-80°C for 5-7 h to obtain an aminated corrosion inhibitor; the aminated corrosion inhibitor, sulfuric acid with a mass fraction of 75%, and deionized water were mixed in a mass ratio of 8-9:12-14:30-31, and the mass fraction of the aminated corrosion inhibitor was uniformly added at 200-300 r / min within 8-10 min. Add 25-35% sodium nitrite solution, continue stirring for 1-2h, add urea of ​​equal mass to the aminated corrosion inhibitor, filter and collect the filtrate to obtain a diazotized corrosion inhibitor; at 0-5°C, pour the diazotized corrosion inhibitor into a coupling treatment solution of 8-10 times the mass of the diazotized corrosion inhibitor at a uniform speed within 8-10min, react for 2-4h, filter, wash with deionized water 3-5 times, and dry at 50-60°C for 8-10h to obtain an ultraviolet absorption intermediate; mix the ultraviolet absorption intermediate, ethanol and 20% sodium hydroxide solution in a mass ratio of 4-5:7-8:9-11, and 8-10 Add ethanol and glucose solution of equal mass at a uniform rate within 10 minutes, react at 50-60°C for 1-3 hours, cool to 40-50°C, add 10% sulfuric acid solution to a pH of 2-4, and filter to obtain a nitrogen oxide intermediate; mix chlorobenzene, ethanol and 14% sulfuric acid solution, nitrogen oxide intermediate, zinc powder and activated carbon in a mass ratio of 18-19:2-3:41-43:8-10:0.3-0.5:5-7, react for 50-70 minutes, filter, wash the oil layer with water until neutral, and vacuum dry at -10-0°C for 22-26 hours to obtain the product.

[0008] The preparation method of the coupling treatment liquid is as follows: p-cresol, deionized water, and sodium dodecylbenzene sulfonate are mixed in a mass ratio of 6-7:90-110:5-6, stirred evenly, and the pH value is adjusted to 7-9 with a sodium hydroxide solution with a mass fraction of 20%.

[0009] The glucose solution is prepared by uniformly mixing glucose and deionized water in a mass ratio of 1:2-3.

[0010] The preparation method of the organic modified aluminum hydroxide is as follows: drying aluminum hydroxide at 110-130° C. for 4-6 hours, cooling to room temperature, mixing aluminum hydroxide and a modified silane coupling agent at a mass ratio of 95-105:1, stirring at 130-150° C. and 2500-3500 r / min for 8-10 minutes to obtain pre-modified aluminum hydroxide; taking 40-60 parts of polyethylene, 90-110 parts of xylene, 3-4 parts of diisopropyl peroxide, and 8-10 parts of a corrosion inhibition monomer by mass; 12 parts, polyethylene and xylene are mixed, stirred at 70-80°C, 200-300r / min for 10-20min, heated to 120-140°C under nitrogen protection, pre-modified aluminum hydroxide is added, stirring is continued, and diisopropylbenzene peroxide is added at a uniform rate within 10-30min, stirred at 250-350r / min for 3-4h, cooled to room temperature, filtered, washed with acetone for 3-5 times, and vacuum dried at -10--1°C for 22-24h.

[0011] The preparation method of the modified silane coupling agent is as follows: chloropropyl triethoxysiloxane and dimethyl allylamine are mixed in a molar ratio of 1:1, immersed in N-methyl pyrrolidone, reacted at 200-300 r / min and 70-90° C. for 10-14 hours, filtered, washed with N-methyl pyrrolidone, 0.08-0.12 mol / L hydrogen chloride solution and methanol for 3-5 times in sequence, and vacuum dried at -10-0° C. for 22-24 hours.

[0012] The beneficial effects of the technical solution provided by the embodiment of the present invention include at least:

[0013] (1) The accelerating setting agent provided by the present invention is used in concrete, which can make the concrete have better comprehensive properties and achieve the effects of rapid setting, low rebound and high pressure resistance.

[0014] (2) In particular, the accelerator provided by the present invention is used in concrete. Due to the presence of the ultraviolet absorber and polyethylene, the durability of the concrete can be improved, the service life of the concrete structure can be extended, and the steel bars in the reinforced concrete can be protected to achieve a corrosion inhibition effect. At the same time, the ultraviolet absorber on the metal chelating agent attached to the surface of the steel bars can conduct the absorbed ultraviolet rays to the outside through the steel bars in summer, accelerating the heat dissipation capacity of the concrete, and can convert the absorbed ultraviolet rays into heat energy in winter to achieve a heat preservation effect; the surface of the organically modified aluminum hydroxide is rich in quaternary ammonium structure, which can make the concrete have mud resistance; the modified silane coupling agent contains quaternary ammonium salt ions, which can enhance the mud resistance of the concrete. DETAILED DESCRIPTION

[0015] In order to make the technical solutions and advantages of the present invention more clear, the embodiments of the present invention will be described in further detail below.

[0016] Further explanation of the technical solution:

[0017] 30-40 parts of aluminum fluorosilicate material, 20-30 parts of aluminum sulfate, 10-20 parts of corrosion inhibitor, stir evenly until completely dissolved, 10-20 parts of magnesium aluminum silicate, 10-15 parts of organically modified aluminum hydroxide, continue stirring until it becomes a uniform suspension system, add 5-10 parts of diethanolamine, 3-5 parts of triethanolamine, and 2-3 parts of propylene glycol.

[0018] Preparation of corrosion inhibitor:

[0019] 1,4,7-triazacyclononane and acetonitrile are uniformly mixed in a mass ratio of 1:12-13, and a tert-butyl bromoacetate solution corresponding to tert-butyl bromoacetate with a molar amount of 2 times that of 1,4,7-triazacyclononane is uniformly added at 0-4°C and 200-300 r / min within 2-4 hours, the temperature is raised to room temperature, stirring is continued for 22-26 hours, filtered, and dried at 80-85°C for 5-7 hours to obtain a pre-modified corrosion inhibitor; the pre-modified corrosion inhibitor, N,N-diisopropylethylamine, 4-bromo-2-nitroaniline and acetonitrile are uniformly mixed in a mass ratio of 1:1.5-2.5:0.5:0.3-0 .5, stirred at 200-300r / min for 22-26h, dried at 80-85℃ for 5-7h, added ethyl acetate 3-5 times the mass of N,N-diisopropylethylamine, washed with deionized water 3-5 times, dried at 70-80℃ for 5-7h to obtain an aminated corrosion inhibitor; mixed the aminated corrosion inhibitor, sulfuric acid with a mass fraction of 75%, and deionized water in a mass ratio of 8-9:12-14:30-31, and added aminated corrosion inhibitor with a mass fraction of 25-3 at a uniform rate within 8-10min at 200-300r / min. 5% sodium nitrite solution, continue stirring for 1~2h, add urea of ​​equal mass to the aminated corrosion inhibitor, filter and collect the filtrate to obtain a diazo corrosion inhibitor; at 0~5℃, pour the diazo corrosion inhibitor into a coupling treatment solution of 8~10 times the mass of the diazo corrosion inhibitor at a uniform speed within 8~10min, react for 2~4h, filter, wash with deionized water 3~5 times, and dry at 50~60℃ for 8~10h to obtain an ultraviolet absorption intermediate; mix the ultraviolet absorption intermediate, ethanol and 20% sodium hydroxide solution in a mass ratio of 4~5:7~8:9~11, and stir for 8~10min. Add ethanol and glucose solution of equal mass at a uniform speed, react at 50-60°C for 1-3h, cool to 40-50°C, add 10% sulfuric acid solution to a pH of 2-4, and filter to obtain a nitrogen oxide intermediate; mix chlorobenzene, ethanol and 14% sulfuric acid solution, nitrogen oxide intermediate, zinc powder and activated carbon in a mass ratio of 18-19:2-3:41-43:8-10:0.3-0.5:5-7, react for 50-70min, filter, wash the oil layer with water until neutral, and vacuum dry at -10-0°C for 22-26h to obtain the product.

[0020] Preparation of coupling treatment solution:

[0021] The method is prepared by mixing p-cresol, deionized water and sodium dodecylbenzene sulfonate in a mass ratio of 6-7:90-110:5-6, stirring evenly, and adjusting the pH to 7-9 with a 20% mass fraction sodium hydroxide solution.

[0022] The glucose solution is prepared by uniformly mixing glucose and deionized water in a mass ratio of 1:2-3.

[0023] Preparation of organic modified aluminum hydroxide:

[0024] Dry the aluminum hydroxide at 110-130°C for 4-6 hours, cool to room temperature, mix the aluminum hydroxide and modified silane coupling agent at a mass ratio of 95-105:1, stir at 130-150°C and 2500-3500 r / min for 8-10 minutes to obtain pre-modified aluminum hydroxide; take 40-60 parts of polyethylene, 90-110 parts of xylene, 3-4 parts of diisopropylbenzene peroxide, and 8-12 parts of pre-modified aluminum hydroxide by mass, and mix the polyethylene Mix olefins and xylene, stir at 70-80°C and 200-300r / min for 10-20min, raise the temperature to 120-140°C under nitrogen protection, add pre-modified aluminum hydroxide, continue stirring, and add diisopropylbenzene peroxide at a uniform speed within 10-30min, stir at 250-350r / min for 3-4h, cool to room temperature, filter, wash with acetone 3-5 times, and vacuum dry at -10--1°C for 22-24h to obtain the product.

[0025] Preparation of modified silane coupling agent;

[0026] Chloropropyltriethoxysiloxane and dimethylallylamine are mixed in a molar ratio of 1:1, immersed in N-methylpyrrolidone, reacted at 200-300 r / min and 70-90°C for 10-14 hours, filtered, washed with N-methylpyrrolidone, 0.08-0.12 mol / L hydrogen chloride solution and methanol for 3-5 times in sequence, and vacuum dried at -10-0°C for 22-24 hours to obtain the product.

[0027] II. Selection of Raw Materials

[0028] Preparation of corrosion inhibitor A

[0029] 1,4,7-triazacyclononane and acetonitrile were mixed uniformly at a mass ratio of 1:12.5, and a tert-butyl bromoacetate solution corresponding to tert-butyl bromoacetate twice the molar amount of 1,4,7-triazacyclononane was uniformly added at 2°C and 250r / min within 3 hours, and the temperature was raised to room temperature, and stirring was continued for 24 hours. The mixture was filtered and dried at 82.5°C for 6 hours to obtain a pre-modified corrosion inhibitor; the pre-modified corrosion inhibitor, N,N-diisopropylethylamine, 4-bromo-2-nitroaniline and acetonitrile were mixed at a mass ratio of 1:2:0. 5:0.4, stirred at 250r / min for 24h, dried at 82.5℃ for 6h, added ethyl acetate 4 times the mass of N,N-diisopropylethylamine, washed 4 times with deionized water, and dried at 75℃ for 6h to obtain an aminated corrosion inhibitor; the aminated corrosion inhibitor, 75% sulfuric acid, and deionized water were mixed at a mass ratio of 8.5:13:30.5, and at 250r / min, 30% of the mass of the aminated corrosion inhibitor was added at a uniform speed within 9min. Sodium nitrite solution, continue stirring for 1.5h, add urea of ​​equal mass to the aminated corrosion inhibitor, filter and collect the filtrate to obtain a diazo corrosion inhibitor; at 2.5°C, pour the diazo corrosion inhibitor into a coupling treatment solution of 9 times the mass of the diazo corrosion inhibitor at a uniform speed within 9min, react for 3h, filter, wash with deionized water 4 times, and dry at 55°C for 9h to obtain an ultraviolet absorption intermediate; mix the ultraviolet absorption intermediate, ethanol and 20% sodium hydroxide solution in a mass ratio of 4.5:7.5:10, Add ethanol and glucose solution of equal mass at a uniform rate within 9 minutes, react at 55°C for 2 hours, cool to 45°C, add 10% sulfuric acid solution with a mass fraction to a pH of 3, and filter to obtain the nitrogen oxide intermediate; mix chlorobenzene, ethanol and 14% sulfuric acid solution, nitrogen oxide intermediate, zinc powder and activated carbon in a mass ratio of 18.5:2.5:42:9:0.4:6, react for 60 minutes, filter, wash the oil layer with water until neutral, and vacuum dry at -5°C for 24 hours to obtain the product.

[0030] Preparation of corrosion inhibitor B

[0031] 1,4,7-triazacyclononane and acetonitrile were mixed uniformly in a mass ratio of 1:12.5, and a tert-butyl bromoacetate solution corresponding to tert-butyl bromoacetate with a molar amount twice that of 1,4,7-triazacyclononane was uniformly added at 2°C and 250 r / min within 3 hours, the temperature was raised to room temperature, stirring was continued for 24 hours, filtered, and dried at 82.5°C for 6 hours to obtain a pre-modified corrosion inhibitor; a 10% mass fraction sulfuric acid solution was added to a pH of 3, washed with water to neutrality, and vacuum dried at -5°C for 24 hours.

[0032] Preparation of organic modified aluminum hydroxide A

[0033] Aluminum hydroxide was dried at 120°C for 5 hours, cooled to room temperature, aluminum hydroxide and modified silane coupling agent were mixed at a mass ratio of 100:1, stirred at 140°C, 3000r / min for 9 minutes to obtain pre-modified aluminum hydroxide; 50 parts of polyethylene, 100 parts of xylene, 3.5 parts of diisopropylbenzene peroxide, and 10 parts of pre-modified aluminum hydroxide were taken by mass, polyethylene and xylene were mixed, stirred at 75°C, 250r / min for 15 minutes, heated to 130°C under nitrogen protection, pre-modified aluminum hydroxide was added, stirring was continued, and diisopropylbenzene peroxide was added at a uniform speed within 20 minutes, stirred at 300r / min for 3.5 hours, cooled to room temperature, filtered, washed with acetone 4 times, and vacuum dried at -5.5°C for 23 hours to obtain.

[0034] Preparation of organic modified aluminum hydroxide B

[0035] Aluminum hydroxide was dried at 120° C. for 5 h, cooled to room temperature, and aluminum hydroxide and modified silane coupling agent were mixed at a mass ratio of 100:1, and stirred at 140° C. and 3000 r / min for 9 min to obtain the product. Example 1

[0036] 35 parts of aluminum fluorosilicate material, 25 parts of aluminum sulfate, 15 parts of corrosion inhibitor A, stir evenly until completely dissolved, 15 parts of magnesium aluminum silicate, 12.5 parts of organically modified aluminum hydroxide A, continue stirring until it becomes a uniform suspension system, add 7.5 parts of diethanolamine, 4 parts of triethanolamine, and 2.5 parts of propylene glycol. Example 2

[0037] 35 parts of aluminum fluorosilicate material, 25 parts of aluminum sulfate, 15 parts of corrosion inhibitor B, stir evenly until completely dissolved, 15 parts of magnesium aluminum silicate, 12.5 parts of organic modified aluminum hydroxide A, continue stirring until it becomes a uniform suspension system, add 7.5 parts of diethanolamine, 4 parts of triethanolamine, and 2.5 parts of propylene glycol. Example 3

[0038] 35 parts of aluminum fluorosilicate material, 25 parts of aluminum sulfate, stir evenly until completely dissolved, 15 parts of magnesium aluminum silicate, 12.5 parts of organic modified aluminum hydroxide A, continue stirring until it becomes a uniform suspension system, add 7.5 parts of diethanolamine, 4 parts of triethanolamine, and 2.5 parts of propylene glycol. Example 4

[0039] 35 parts of aluminum fluorosilicate material, 25 parts of aluminum sulfate, 15 parts of corrosion inhibitor A, stir evenly until completely dissolved, 15 parts of magnesium aluminum silicate, 12.5 parts of organic modified aluminum hydroxide B, continue stirring until it becomes a uniform suspension system, add 7.5 parts of diethanolamine, 4 parts of triethanolamine, and 2.5 parts of propylene glycol. Example 5

[0040] 35 parts of aluminum fluorosilicate material, 25 parts of aluminum sulfate, 15 parts of corrosion inhibitor A, stir evenly until completely dissolved, 15 parts of magnesium aluminum silicate, 12.5 parts of aluminum hydroxide continue to stir until a uniform suspension system is formed, add 7.5 parts of diethanolamine, 4 parts of triethanolamine, and 2.5 parts of propylene glycol.

[0041] Performance Test:

[0042] Compressive strength: The test is carried out in accordance with the "Standard for Test Methods of Physical and Mechanical Properties of Concrete" (GB / T 50081-2019). The cube compressive strength of the test for 1 day = 0.95*specimen failure load / specimen pressure-bearing surface area*100%;

[0043] Rebound test: adopt the large plate method, make a 60cm*60cm*20cm large plate test mold, set the spraying amount at 185kg concrete each time, clean and weigh the concrete that falls off on the ground after spraying, and calculate its percentage of the total spraying amount as the rebound rate of the sprayed concrete, rebound rate = measured value of rebound weight / spraying weight estimated or measured according to the mix ratio*100%;

[0044] Anti-cracking test: According to the Standard for Test Methods of Long-term Performance and Durability of Ordinary Concrete (GB / T50082-2009), a flat thin plate specimen with a size of 800mm*600mm*100mm was made. After the specimen was formed, the wind direction was parallel to the specimen surface and the crack inducing ribs, and the wind speed was controlled at 4.5~5.5m / s. The test time started from the mixing of concrete with water, and the number of cracks was recorded 36 hours after the specimen was formed.

[0045] Corrosion inhibition experiment: Take 6 steel bars with a diameter of 3 cm and a length of 10 cm, weigh and record the initial mass m1 of the steel bars, immerse the weighed steel bars in 6 groups of cement respectively, let stand for 72 hours, and prepare reinforced concrete samples. Immerse the reinforced concrete samples in a hydrochloric acid aqueous solution with a mass fraction of 12%, let stand for 72 hours, take out, take out the steel bars from the concrete samples, remove the concrete on the surface of the steel bars, weigh and record the mass m2 of the steel bars, and calculate the corrosion rate of the steel bars. The corrosion rate of the steel bars = (m1-m2) / m1*100%;

[0046] Durability test: Based on the "quick freezing method" in the "Standard for Test Methods of Long-term Performance and Durability of Ordinary Concrete" (GB / T50082-2009), the 100mm*100mm*400mm rectangular specimens that have been cured for 24 days in a constant temperature and humidity curing box are taken out of the curing box, and then the specimens are soaked in clean water at a temperature of 17~23℃. The water surface should be 20~30mm higher than the top surface of the specimen during soaking. After soaking in clean water for 3~5 days, the specimens are taken out and the excess water on the surface of the specimens is wiped off with a wet cloth. The initial dynamic elastic modulus and mass are tested, and then the specimens are placed in a freeze-thaw cycle tester for a clean water freeze-thaw cycle test. The number of freeze-thaw cycles is 200 to calculate the mass loss rate. The test results are shown in Table 1:

[0047] Table 1

[0048]

[0049] As can be seen from Table 1, the quick-setting agent for reducing the rebound of shotcrete prepared by the present invention has excellent comprehensive performance, can make concrete have better comprehensive performance, and can achieve the effects of quick setting, low rebound and pressure resistance; and due to the introduction of ultraviolet absorber, the durability of concrete is enhanced, and the service life of concrete structure buildings is extended; due to the introduction of metal chelating agent and trifluoromethyl, the corrosion inhibition ability of concrete is enhanced, and the service life of concrete structure buildings is extended; the ultraviolet absorber grafted with metal chelating agent can conduct the absorbed ultraviolet rays to the outside world through the steel bar heat in summer, accelerate the heat dissipation capacity of concrete, and can convert the absorbed ultraviolet rays into heat energy in winter, achieve thermal insulation effect, and extend the service life of concrete structure buildings; modified organic modified aluminum hydroxide is grafted with polyethylene, and polyethylene can improve the durability of concrete and extend the service life of concrete structure buildings.

[0050] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A quick-setting agent for reducing the rebound of shotcrete, characterized in that: The raw material components include the following parts by weight: 30-40 parts of aluminum fluorosilicate material, 20-30 parts of aluminum sulfate, 10-20 parts of corrosion inhibitor, stir evenly until completely dissolved, 10-20 parts of magnesium aluminum silicate, 10-15 parts of organic modified aluminum hydroxide, continue stirring until it becomes a uniform suspension system, add 5-10 parts of diethanolamine, 3-5 parts of triethanolamine, and 2-3 parts of glycerol; The preparation method of the corrosion inhibitor is as follows: 1,4,7-triazacyclononane and acetonitrile were mixed uniformly in a mass ratio of 1:12-13, and a tert-butyl bromoacetate solution corresponding to tert-butyl bromoacetate twice the mass of 1,4,7-triazacyclononane was uniformly added at 0-4°C and 200-300 r / min within 2-4 hours, and the mixture was heated to room temperature, stirred for 22-26 hours, filtered, and dried at 80-85°C for 5-7 hours to obtain a pre-modified corrosion inhibitor; the pre-modified corrosion inhibitor, N,N-diisopropylethylamine, 4-bromo-2-nitroaniline and acetonitrile were mixed in a mass ratio of 1:1.5-2.5:0.5:0.3-0. 5, stirred at 200-300 r / min for 22-26 h, dried at 80-85 °C for 5-7 h, added ethyl acetate 3-5 times the mass of N,N-diisopropylethylamine, washed with deionized water 3-5 times, and dried at 70-80 °C for 5-7 h to obtain an aminated corrosion inhibitor; the aminated corrosion inhibitor, 75% sulfuric acid, and deionized water were mixed in a mass ratio of 8-9:12-14:30-31, and the aminated corrosion inhibitor was added at a uniform rate of 25-35 mass fraction at 200-300 r / min within 8-10 min. % sodium nitrite solution, continue stirring for 1~2h, add urea of ​​equal mass to the aminated corrosion inhibitor, filter and collect the filtrate to obtain a diazotized corrosion inhibitor; at 0~5℃, pour the diazotized corrosion inhibitor into a coupling treatment solution of 8~10 times the mass of the diazotized corrosion inhibitor at a uniform speed within 8~10min, react for 2~4h, filter, wash with deionized water 3~5 times, and dry at 50~60℃ for 8~10h to obtain an ultraviolet absorption intermediate; mix the ultraviolet absorption intermediate, ethanol and 20% sodium hydroxide solution in a mass ratio of 4~5:7~8:9~11, and precipitate within 8~10min. Add ethanol and glucose solution of equal mass at a uniform rate, react at 50-60°C for 1-3h, cool to 40-50°C, add 10% sulfuric acid solution to a pH of 2-4, and filter to obtain a nitrogen oxide intermediate; mix chlorobenzene, ethanol and 14% sulfuric acid solution, nitrogen oxide intermediate, zinc powder and activated carbon in a mass ratio of 18-19:2-3:41-43:8-10:0.3-0.5:5-7, react for 50-70min, filter, wash the oil layer with water until neutral, and vacuum dry at -10-0°C for 22-26h to obtain; The preparation method of the organic modified aluminum hydroxide is as follows: The aluminum hydroxide is dried at 110-130°C for 4-6 hours, cooled to room temperature, and the aluminum hydroxide and modified silane coupling agent are mixed at a mass ratio of 95-105:1, and stirred at 130-150°C and 2500-3500 r / min for 8-10 minutes to obtain pre-modified aluminum hydroxide; 40-60 parts of polyethylene, 90-110 parts of xylene, 3-4 parts of diisopropylbenzene peroxide, and 8-12 parts of corrosion inhibition monomer are taken by mass, and the polyethylene and xylene was mixed, stirred at 70-80°C and 200-300 r / min for 10-20 min, heated to 120-140°C under nitrogen protection, pre-modified aluminum hydroxide was added, stirring was continued, and diisopropylbenzene peroxide was added at a uniform speed within 10-30 min, stirred at 250-350 r / min for 3-4 h, cooled to room temperature, filtered, washed with acetone for 3-5 times, and vacuum dried at -10--1°C for 22-24 h to obtain the product; The preparation method of the coupling treatment solution is as follows: The method is prepared by mixing p-cresol, deionized water and sodium dodecylbenzene sulfonate in a mass ratio of 6-7:90-110:5-6, stirring evenly, and adjusting the pH to 7-9 with a 20% mass fraction sodium hydroxide solution.

2. The quick-setting agent for reducing the rebound of shotcrete according to claim 1, characterized in that: The glucose solution is prepared by uniformly mixing glucose and deionized water in a mass ratio of 1:2-3.

3. The quick-setting agent for reducing the rebound of shotcrete according to claim 1, characterized in that: The preparation method of the modified silane coupling agent is as follows; Chloropropyltriethoxysiloxane and dimethylallylamine are mixed in a molar ratio of 1:1, immersed in N-methylpyrrolidone, reacted at 200-300 r / min and 70-90°C for 10-14 hours, filtered, washed with N-methylpyrrolidone, 0.08-0.12 mol / L hydrogen chloride solution and methanol for 3-5 times in sequence, and vacuum dried at -10-0°C for 22-24 hours to obtain the product.

Citation Information

Patent Citations

  • Normal-temperature preparation method of alkali-free liquid accelerator for quick-hardening early-strength sprayed concrete

    CN115572099A